The Influence of Workload and Work Environment on Employee Performance - Hansah, Adi (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2025)
The purpose of this research is to determine and analyze: (1) Workload (2) Work Environment; (3) Employee Performance; and (4) the Influence of Workload and Work Environment on Employee Performance at the X Office in West Java Province, both simultaneously and partially. The research methods used in this study are descriptive surveys and explanatory surveys, with the unit of analysis being the employees at the X Office in West Java Province, with a sample size of 30 people. The type of investigation is causality, and the time horizon in this study is cross-sectional. Based on the research results, it was found that the Workload experienced by Employees of Office X in West Java Province is already good, the Work Environment at Office X in West Java Province can generally be considered good, and the Performance of Employees at Office X in West Java Province is currently rated as good. Workload and Work Environment simultaneously and partially affect Employee Performance at Dinas X in West Java Province. However, partially, Workload has a more dominant influence on Employee Performance than Work Environment. Because Workload more dominantly affects Performance, it becomes the top priority in improving that Performance. Therefore, employees of the X Office in West Java Province are advised to improve the working conditions and atmosphere, so they can work more professionally.